2022
DOI: 10.7717/peerj.13238
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes and ferroptosis: roles in tumour regulation and new cancer therapies

Abstract: Research on the biological role of exosomes is rapidly developing, and recent evidence suggests that exosomal effects involve ferroptosis. Exosomes derived from different tissues inhibit ferroptosis, which increases tumour cell chemoresistance. Therefore, exosome-mediated regulation of ferroptosis may be leveraged to design anticancer drugs. This review discusses three pathways of exosome-mediated inhibition of ferroptosis: (1) the Fenton reaction; (2) the ferroptosis defence system, including the Xc-GSH-GPX4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 215 publications
0
8
0
Order By: Relevance
“…Developing a better understanding and evaluation of ferroptosis pattern may help guide treatment strategies and improve prognosis of BCa patients (Xia et al, 2022). Based on the co-action and influence of TME, recent evidence suggests that exosome effects involve ferroptosis (Shi et al, 2022). In bladder cancer, our study for the first time combined the role of exosome with ferroptosis, and found the inhibitory effect of exosome miR-217 on ferroptosis in bladder cancer cells, which is a new breakthrough in the mechanism of bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Developing a better understanding and evaluation of ferroptosis pattern may help guide treatment strategies and improve prognosis of BCa patients (Xia et al, 2022). Based on the co-action and influence of TME, recent evidence suggests that exosome effects involve ferroptosis (Shi et al, 2022). In bladder cancer, our study for the first time combined the role of exosome with ferroptosis, and found the inhibitory effect of exosome miR-217 on ferroptosis in bladder cancer cells, which is a new breakthrough in the mechanism of bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Iron accumulation leads to ROS production through the Fenton reaction, resulting in nonenzymatic lipid peroxidation. 42 Fe 3+ in blood circulation binds to transferrin and moves into cells through the transferrin receptor (TFRC), then Fe 3+ is translated into Fe 2+ in endosomes. 43 The divalent metal transporter 1 (DMT1) is responsible for the Fe 2+ secretion from endosomes to the labile iron pool in cells and enhances the Fenton reaction to induce ferroptosis.…”
Section: Exosomes Control Iron Metabolismmentioning
confidence: 99%
“…As its name suggests, ferroptosis depends on cellular iron levels to a great extent. Iron accumulation leads to ROS production through the Fenton reaction, resulting in nonenzymatic lipid peroxidation 42 . Fe 3+ in blood circulation binds to transferrin and moves into cells through the transferrin receptor (TFRC), then Fe 3+ is translated into Fe 2+ in endosomes 43 .…”
Section: The Mechanisms Of Exosomes In Regulating Ferroptosismentioning
confidence: 99%
“…The pro‐ferroptosis effect of EVs accounts for their pathological roles in inflammatory or degenerative diseases and chronic injury. Besides, engineered EVs targeted in triggering ferroptosis are designed and applied for cancer therapy, which efficiently promotes the death of tumor cells 108 . On the other hand, therapeutic EVs are considered to have many merits, such as anti‐inflammatory, anti‐oxidative, and pro‐proliferate properties.…”
Section: Evs Affect the Fate Of Cell Ferroptosismentioning
confidence: 99%
“…Besides, engineered EVs targeted in triggering ferroptosis are designed and applied for cancer therapy, which efficiently promotes the death of tumor cells. 108 On the other hand, therapeutic EVs are considered to have many merits, such as anti-inflammatory, anti-oxidative, and pro-proliferate properties. It also revealed that EVs targeted at iron-associated proteins protect against ferroptosis via the delivery of functional RNAs or proteins.…”
Section: Evs Affect the Fate Of Cell Ferroptosismentioning
confidence: 99%